Dry on vine San Juan´s experiences: compendium of studies - Espindola, Rodrigo Sebastian (2019)
This compendium is the result of all the research and experiences carried out not only by the Grape Raisin Producer and Exporter Group of the Chamber of Foreign Trade of San Juan, Argentina, but also by INTA (National Institute of Agricultural Technology), UNSJ (San Juan National University) and COVIAR (Argentine Viticulture Corporation). These activities started in 2007 with the ‘First International Symposium on Table Grapes and Raisins’ organized by INTA, in which the topic Dry On Vine (DOV) was formally introduced in Argentina by Dr. Matthew Fidelibus (UC Davis Researcher). In the last five years, the joint effort has allowed an improvement in the adoption of technology between grape producers for raisins and industrialists. Today there are over 30 raisin farmers that use DOV: Hector Alos, Gonzalo Huertas, Carlos Huertas, Giselle Alves, Enrique Meló, Guillermo Meló, Patricio Meglioli, Julio Pacheco, Martín Pantano, Marcelo Pomeranchic, Hugo Crescentino, Silvana Putelli, Guillermo Podestá, Ezequiel Cusnir, Jorge Escobar, Jose Murgic, Juan Carlos Reverendo, Alfredo Chiconi, Alfredo Ferre, Fernando Navas and Sergio Rossi, among others. This compendium includes studies on this technology, the opinion of five innovative producers of the San Juan raisin sector, and the recommendations of Mathew Fidelibus, expert of the ‘Kearny Research and Extension Center of the University of California, Davis. DOV technology is considered to be new in San Juan, Argentina, not in others countries like Australia, and United States. It is thought to be a labor-saving technological alternative. It is important to state that the transformation of the traditional raisin production system into DOV requires studying and training since it is necessary to generate a cultural change in the conception of pruning systems within the leading systems. One of the most important difficulties to face will not be the use of technology, but the habit of those who handle pruning shears. DOV technology represents a real strategy to generate cost savings, optimization of land use, and high quality raisins. These factors, taken as a competitive advantage, will allow greater aptitude and better access to the international market. This compendium is divided into chapters in the following order: I) General information about the DOV system and raisin production systems; II) Local studies on the Superior Seedless variety; III) Local studies on the Flame Seedless variety; IV) Quality of DOV raisins; V) The experience of the local producers, and VI) Tips to build a DOV system, and final conclusions. In some sections, the aim is to simplify the wording to facilitate understanding; however, technical vocabulary is generally used. Readers will be able to draw their own conclusions about the economic and technical convenience of using DOV systems. It is not necessary to read Chapter I to understand the rest of the content of thiscompendium. This chapter is a bibliographic compilation that details economic and technical aspects for those who wish to deepen aspects of the application of DOV.